(untitled) (Argos, 2017)
The account of the shrine of Jupiter Pistor (Ov. Fast. 6.349-394) posits that this site was built in acknowledgment of the god’s help during the Gallic siege of Rome. Rome is presented as a defeated city and the construction of this defeat is closely linked with the treatment of space throughout the story. Moreover, such spatial arrangement shows a remarkable inclusion of epic stages. We intend to show that, by moving away from elements and topics that are characteristic of the epic genre and towards/into the genre of elegy, the account displays the genre procedures that make up the poem.